Discovering Environmental Attitude and Lifestyle Segmentation of Green Consumers: a Conceptual Model for Research - Ratchaneekorn Dansirichaisawat (My University, 2014)
The primary purpose of this research is to reviews the literature on green consumers segments with different profiles. It utilizes two constructs–environmental attitude and lifestyle- in the context of electric appliances products in Thailand. This research employs an empirical study by means of the questionnaire survey method to verify the hypotheses. Data will be collected by random sampling from working aged male and female customers who purchased electric appliances. The data will be analyzed using factor analysis, cluster analysis, discriminant and ANOVA. The usefulness of this research was identifying groups of similar customers and potential customers; to prioritize the groups to address; to understand their behavior; and to respond with appropriate marketing strategies.
Keywords: Empirical Research; Market Segmentation; Research method; Environmental Sustainability in Business